EVALUASI KESESUAIAN LAHAN CABAI MERAH DI KAWASAN RELOKASI SIOSAR KABUPATEN KARO - Agustoni Tarigan; Abdul Rauf; R Rahmawaty (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Siosar relocation Region is located in the Subdistrict Merek in Karo with an altitude between 1490 - 1562 m above sea level. With this type of soil Andisol where land is hilly and undulating with a slope of + 37.5% and the climate type D3, leasing land from the Ministry of Environment and Forests covering an area of 414.44 ha reserved for heads of household 370 victims of the eruption of Mount Sinabung, through Decree of the Minister of the Environment life and Forestry No. SK.107 / MenLHK-II / 2015. This study aimed to evaluate the characteristics of the level of production forest land suitability for the cultivation of chilli in the Region Siosar, to analyze the remedial efforts that need to be done in improving crop productivity, and to create maps of the actual land suitability and potential land suitability chilli plants. The method used was a survey method. Unit of land based on soil map consisted of 7 units of land analysis were used for matching. The results showed that the level of potential land suitability for chilli plant (Capsicum annum) included marginally suitable (S3) covering an area of 297,3 ha and quite suitable (S2) covering 117,14 ha.